2000
DOI: 10.2527/2000.782391x
|View full text |Cite
|
Sign up to set email alerts
|

Lysine uptake by mammary gland tissue from lactating sows.

Abstract: Kinetic properties and substrate specificity of the lysine transport system in porcine mammary gland were studied using mammary tissue explants from nine lactating sows. Sodium dependence of lysine uptake was determined by replacing sodium in the medium with choline. Kinetic parameters of lysine uptake were determined using lysine concentrations from 5 microM to 5.12 mM. Competition of lysine uptake by other amino acids was determined using the cationic amino acids, arginine and ornithine, and using other esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 16 publications
0
15
1
Order By: Relevance
“…Amino acid extraction rates (%) across the porcine mammary glands in relation to day of lactation a 0.96% as compared with 0.67% in the study by Trottier et al (1997). Hurley et al (2000) demonstrated that in vitro lysine uptake in the sow mammary tissue occurred via a sodium-independent transport mechanism with a Km of 1.4 mM, which was approximately 10-fold higher than the arterial plasma concentration of lysine found in this study. Thus, the lack of variation in lysine A-VD by no means indicates that lysine uptake was saturated during the stage of lactation period studied herein.…”
Section: Resultscontrasting
confidence: 43%
“…Amino acid extraction rates (%) across the porcine mammary glands in relation to day of lactation a 0.96% as compared with 0.67% in the study by Trottier et al (1997). Hurley et al (2000) demonstrated that in vitro lysine uptake in the sow mammary tissue occurred via a sodium-independent transport mechanism with a Km of 1.4 mM, which was approximately 10-fold higher than the arterial plasma concentration of lysine found in this study. Thus, the lack of variation in lysine A-VD by no means indicates that lysine uptake was saturated during the stage of lactation period studied herein.…”
Section: Resultscontrasting
confidence: 43%
“…Cationic amino acids are actively transported into the lactating mammary gland by Na + -independent transport systems [46][47][48][49], but the cationic amino acid transporters have been poorly described in the mammary gland [28,50]. In this study, CAT-1 mRNA abundance increased during lactation when compared with the virgin rats.…”
Section: Discussionmentioning
confidence: 48%
“…For example, low affinity transport with a K M in excess of 1 . 0 mmol/litre has similarly been described for lysine in porcine mammary tissue (Hurley et al 2000). These authors also indicated the possibility of a more complex analysis of kinetic data to that of the single saturable curve used in their work.…”
Section: Discussionmentioning
confidence: 70%